2008
DOI: 10.1016/j.yqres.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of stalagmite-derived Asian summer monsoon records from North Atlantic temperature change during marine oxygen isotope stage 5d

Abstract: The Asian monsoon is an important component of the global climate system. Seasonal variations in wind, rainfall, and temperature associated with the Asian monsoon systems affect a vast expanse of tropical and subtropical Asia. Speleothem-derived summer monsoon variation in East Asia was previously found to be closely associated with millennial-scale change in temperature in the North Atlantic region between 75 and 10 ka. New evidence recovered from East Asia, however, suggests that the teleconnection between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 30 publications
0
23
0
4
Order By: Relevance
“…This notion is opposite to what was observed in this study and as shown in Figure 1. With respect to Sr, the experiments by Kinsman and Holland [18] and Lorens [20] indicate that temperature and growth rates of calcite may affect Sr in SZ2 via distribution coefficients, and the Sr content of SZ2 seems to agree with the growth rate of SZ2 [17]. However, as mentioned above, no consistent results have been derived from these experiments.…”
Section: Influences Via Distribution Coefficientsmentioning
confidence: 92%
See 2 more Smart Citations
“…This notion is opposite to what was observed in this study and as shown in Figure 1. With respect to Sr, the experiments by Kinsman and Holland [18] and Lorens [20] indicate that temperature and growth rates of calcite may affect Sr in SZ2 via distribution coefficients, and the Sr content of SZ2 seems to agree with the growth rate of SZ2 [17]. However, as mentioned above, no consistent results have been derived from these experiments.…”
Section: Influences Via Distribution Coefficientsmentioning
confidence: 92%
“…Although the growth rate of SZ2 changed remarkably over time [17], this should not be a significant mechanism affecting Mg in SZ2 [21,23]. Thus, the most probable mechanism affecting Mg in SZ2 via distribution coefficients may be temperature.…”
Section: Influences Via Distribution Coefficientsmentioning
confidence: 95%
See 1 more Smart Citation
“…Behl and Kennett (1996) discussed the connections of anoxic events in the Santa Barbara basin with the Dansgaard-Oeschger warm interstadials recorded in the GISP2 core for the past 60 kyr, and Wang et al (2008) discussed the strong coupling between the East Asian Summer Monsoon system and the North Atlantic, especially during the cold glacial interval between 75 to 10 kyr BP. However, different regions may not be so optimally teleconnected at a much warmer interglacial time when there is little Arctic or Northern Hemisphere volume of ice, such as during the MIS stage 5d (Zhou et al, 2008).…”
Section: The Solar Arctic-mediated Climate Variation On Multidecadal mentioning
confidence: 99%
“…Carbonate rocks are common in China, and the monsoon climate favors the development of caves and speleothems. Over the past decade, speleothem research in China has greatly improved our understanding of the history and variability of the Asian monsoon (e.g., Wang et al 2001Wang et al , 2005Wang et al , 2008Tan et al 2003Tan et al , 2009Tan et al , 2011Yuan et al 2004;Dykoski et al 2005;Cai et al 2006Cai et al , 2010aCai et al , b, 2012Zhou et al 2008;Cheng et al , 2012. For example, stalagmite oxygen isotopic records from China have revealed the patterns of variations in the Asian monsoon over the last 500 ka years (Yuan et al 2004;Wang et al 2008;Cheng et al 2009Cheng et al , 2012.…”
Section: Introductionmentioning
confidence: 99%